Diversification of Domestic and Foreign Models of Vocational Training Institutions Rating - Ivanenko, Nina A.; Perezhogina, Olga N.; Komelina, Valentina A.; Mishchenko, Vladimir A.; Parkhaev, Viktor T.; Fatykhova, Liliya I.; Mullagaliev, Adel R.; Litvin, Irina Y. (International Review of Management and Marketing, 2016)
With the joining to the Bologna Process Russian universities go out to the world market of educational services, where they will have to compete with foreign universities. In this connection the problem of various models' study of vocational training institutions' ratings is especially important. This article aims to identify the advantages and disadvantages of both foreign and domestic ratings. The leading method in the study of this problem is the comparative method, which allowed identify the distinctive features and the similarities of sites offering universities' and colleges' various rankings. In the article the types of ratings by type, structure and data sources are presented; advantages and disadvantages of foreign and domestic rankings of universities and colleges are identified, the content of national sites that offer ratings of various models is generalized. Keywords: diversification, domestic and foreign ratings, site, educational institutions JEL Classifications: F50; F55; I2; I25